Management of Type III palatogingival groove in permanent maxillary lateral incisor with intentional replantation - Aaliya Rehman; Huma Iftekhar; Rajendra Kumar Tewari; Surendra Kumar Mishra (Wolters Kluwer Medknow Publications, 2022)
A palatogingival groove (PGG) is a developmental deformity that may cause a severe periodontal breakdown or combined endodontic and periodontal defect. In the present case, a 24-year-old patient reported a complaint of pain in the upper left front tooth region for 3 months. Clinical and radiological examination revealed a PGG in the permanent maxillary left lateral incisor. Cone-beam computed tomography showed multiple shallow grooves on the root surface and a deep palatal groove extending to the apex. Interdisciplinary management comprising endodontic therapy and intentional replantation was formulated. After endodontic procedure, tooth #22 was gently extracted. The shallow grooves were removed by odontoplasty. A Class II cavity was made in the deep palatal groove and was connected with the root-end preparation. The cavity was sealed with biodentin up to the cementoenamel junction and the coronal portion was sealed with light-cured glass-ionomer cement. The tooth was replanted in socket and splinted for 7 days. Follow-up visits revealed the functional status of tooth and complete bony healing. Tooth discoloration was successfully managed with intracoronal bleaching with sodium perborate. A 12-month radiographic follow-up revealed no evidence of root resorption or ankylosis.